IMPLEMENTASI PEMBELAJARAN JARAK JAUH PADA KOMPETENSI KEAHLIAN TEKNIK KENDARAAN RINGAN OTOMOTIF DI SMKN 1 SEDAYU - Rino Suasono Edi (Jurnal Pendidikan Vokasi Otomotif, 2022)
This study aims to describe the implementation of PJJ, the constraints of teachers, students, and parents/guardians, and the role of parents/guardians in accompanying students during PJJ. This research is descriptive qualitative and quantitative research. Subjects included 5 TKRO teachers, students of 27 TKRO grade XI, and their parents/guardians. The data collection used questionnaire and interviews and it was supported by documentation. The instrument validity test was carried out through expert judgment. The data presented with diagrams and percentages from the results of the questionnaire instrument. Based on the results of the study, it was concluded that: (1) the implementation of PJJ at the planning stage through teacher perceptions went well because the teacher carried out PJJ activities according to government regulations. The stage of implementing PJJ through perception of teachers, students, and parents/guardians has been done optimally, but they hope that the pandemic will end soon. 55.6% of students and 85.2% of parents/guardians chose face-to-face learning. (2) the obstacles faced by teachers during the PJJ processes were regarding the difficulty of obtaining teaching materials with high credibility. 63% of students complained they were too many assignments and 51.9% of parents/guardians complained to buy internet quota and had difficulty operating gadgets. (3) the role of parents/guardians in assisting students during PJJ has been implemented, supported by data from 66.7% of parents/guardians helping their son/daughter if they have learning difficulties.